Data Dictionaries: Essential Tools for the Ethical and Transparent Use of Integrated Data - Pepe, Rebecca S.; Coe, Kristen (International journal of population data science, 2025)
Data transparency lays the groundwork for the ethical use of administrative data. This is particularly true for linked administrative data within integrated data systems (IDS). Data dictionaries, resources that maintain the metadata of the information housed in an IDS, offer a tool to ensure transparency throughout the data life cycle. The FAIR Principles, which assert that data be Findable, Accessible, Interoperable, and Reusable provide a useful framework by which to measure the effectiveness of data dictionaries in the IDS context. This paper uses the FAIR Principles to discuss the ways in which data dictionaries serve as tools in the ethical and transparent use of integrated data as well as the challenges that remain. Linked administrative data is a valuable source of information for programmatic and academic research. Data dictionaries facilitate the ethical handling of this sensitive information and maintain a commitment to transparency in data inquiry and research.